Ontological Problems of the Relationship Between Virtuality and Reality - Avetisyan, Ghazar (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The article discusses issues related to the relationship between virtuality and reality, through comparative analysis reveals the foundations of the ontological distinction between reality as the outside world and virtuality. An attempt is made to determine the ontological status of virtuality in the system of being. The purpose of the article is to reveal the position of virtuality in the ranking of realities, similarities and differences with material reality, as well as promising opportunities and challenges. In the article, special attention is paid to clarifying the concept of virtuality, an attempt is made to describe the entire range of manifestations that this concept covers. Issues such as physically insurmountable ontological boundaries, concepts of conditional and mental realities in the context of attitudes to virtuality are discussed. In order to assess the ontological status of virtuality, the creation of virtual objects, their dependence on physical reality, autonomy, imagery, interactivity of virtual worlds, as well as the degree of reliability and stability are considered. As a result of the discussion, it turns out that virtuality is inferior to physical reality in integrity, sensory perception, saturation, lack of complete independence and a number of other aspects without the goal of overcoming this reality, competing with it or going beyond it.